Antidepressant-like effects of agmatine and NOS inhibitors in chronic unpredictable mild stress model of depression in rats: The involvement of NLRP inflammasomes - ARICIOĞLU, FEYZA (ELSEVIER, 2019)
Innate immunity activation in the central nervous system (CNS) is known to contribute to the development of depression through NOD-like receptors containing pyrin domain 3 (NLRP3) inflammasome assembly. Furthermore, administration of agmatine (AGM), a nitric oxide synthase (NOS) inhibitor, reverses stress-induced NLRP3 inflammasome activation in rats. We examined the effects of chronically-administered nitric oxide (NO) pathway modulating drugs on NLRP1/3-mediated neuroinflammatory responses and depressive-like behaviors in chronic unpredictable mild stress (CUMS) depression model of rats. CUMS model was applied to the adult male Sprague-Dawley rats for 6 weeks and the treatments were daily administered via intraperitoneal route in the last 3 weeks of CUMS procedure. Depressive-like behaviors were assessed by sucrose preference and forced swimming tests. The levels of NLRP inflammasome components (NLRP1, NLRP3, ASC, caspase-1 and IL-1 beta) were investigated in the prefrontal cortex by real time PCR and western blot methods. CUMS-induced depressive-like behaviors were coupled with the overactivation of NLRP1 and NLRP3 inflammasome sensors and increased levels of IL-1 beta. Depressive-like behaviors were ameliorated by chronic AGM and NOS inhibitor treatments. AGM and other NOS inhibitor treatments were found to be more effective in suppressing NLRP3 and NLRP1, respectively. All inhibitor reagents downregulated inflammasome components and IL-1 beta. These results suggest that both neuronal NLRP1 and microglial NLRP3 inflammasomes are involved in chronic stress-induced depressive-like behaviors. The antidepressant effects of AGM, iNOS and nNOS inhibitors are associated with the downregulation of CNS inflammasome expression levels. NO-pathway modulating drugs might provide novel therapeutic strategies for depression.
Keywords: Depression; inflammasome; NLRP1; NLRP3; Agmantine; NOS inhibitors; NITRIC-OXIDE SYNTHASE; ANIMAL-MODEL; MOUSE MODEL; ACTIVATION; INFLAMMATION; BEHAVIOR; RECEPTORS; SYSTEM; MICE; PATHOPHYSIOLOGY